Ancestry-Specific Interactions Between Circulatory Folate and One-Carbon Metabolism Genes' Haplotypes for Higher-Grade Cervical Intraepithelial Neoplasia. (7th June 2021) - Wijayatunga, Nadeeja; Ding, Lili; Piyathilake, Chandrika
Abstract: Objectives: Determine ancestry-specific interactions between circulatory folate concentrations, haplotypes of the one-carbon (1C) pathway genes and risk of higher-grade cervical intraepithelial neoplasia (CIN2+) in the US post-folic acid fortification era. Methods: Study included self-reported African American and Caucasian American women positive for high-risk human papillomavirus (HPV) genotypes and diagnosed with ≤ CIN1 (non-cases, n  = 340) or CIN2+ (cases, n  = 337). Plasma and red blood cell (RBC) folate, vitamins B12 (B12) and C, and total carotene levels were measured. 660 single nucleotide polymorphisms of the 1C pathway genes and 104 ancestry informative markers (AIMs) were analyzed using buffy coat DNA and customizable Illumina GoldenGate arrays. Global African ancestry (GA) was estimated using the AIMs. Ancestry-based African American (AFR) had GA ≥ 0.8 and European Americans (EA) otherwise. Common haplotype blocks ( n  = 50) were tested for interactions with circulatory folate using logistic regression adjusting for age, education, body mass index (BMI), body fat %, smoking, parity, hormonal contraception use, plasma total carotene, B12 and C. False discovery rate < 0.1 was considered significant. Results: Some of the main findings were, increasing plasma folate (1 SD) decreases the risk of CIN2 + when homozygous for haplotype CG at (rs575425, rs586199) of BHMT gene in EA (odds ratio/OR = 0.13, CI = 0.04, 0.44), and for haplotype TA at (rs559062, rs515064) of CTH in AFR (OR = 0.23, CI = 0.1, 0.52); increasing RBC folate (1 SD) decreases risk of CIN2 + when homozygous for haplotypes TA at (rs559062, rs515064) of CTH (OR = 0.27, CI = 0.12, 0.61), AC at (rs7706298, rs10512934) of MTRR (OR = 0.21, CI = 0.08, 0.57), and AGA at (rs11672909, rs759920, rs7253062) of DNMT1 (OR = 0.4, CI = 0.18, 0.90) in AFR; and increasing RBC folate (1 SD) increases the risk of CIN2 + when homozygous for haplotypes GG at (rs3856027, rs4650051) of CTH gene (OR = 3.52, CI = 1.27, 9.71), and CGG at (rs11672909, rs759920, rs7253062) of DNMT1 (OR = 5.70, CI = 1.86, 17.49) in AFR. Conclusions: Circulatory folate differentially modulates the risk for CIN2 + by interacting with haplotypes of the 1C pathway genes according to ancestry in reproductive-aged women exposed to US folic acid fortification program. Funding Sources: National Cancer Institute